Challenges and Silver Linings of COVID-19 in Ethiopia –Short Review - Wondimu W; Girma B (Journal of Multidisciplinary Healthcare, 2020)
Wondimagegn Wondimu,1 Bethlehem Girma2 1Department of Public Health, College of Medicine and Health Sciences, Mizan-Tepi University, Mizan Aman, Ethiopia; 2Department of Health Extension Program, Mizan Aman Health Science College, Mizan Aman, EthiopiaCorrespondence: Wondimagegn Wondimu(MPH in Epidemiology), Mizan-Tepi University, College of Medicine and Health Sciences, Department of Public Health, P.O. Box: 260, Mizan Aman, EthiopiaEmail wonde1983.ww@gmail.comAbstract: Difficult situations bring not only challenges but also fruitful opportunities. The pandemic of COVID-19 by itself and the related governmental or individual level measures have their own challenges and opportunities to the community, which even might be directly or indirectly related to the control and prevention of the pandemic. The silver linings of the pandemic of COVID-19 should be uncovered to encourage the community not only to focus on the black side of the disease but also to enjoy the opportunities. This can contribute to facilitate the control of the disease and avoid the related panics. In this review, we have discussed the challenges of COVID-19 in Ethiopia in terms of health, economy, and social life, and the silver linings in terms of research opportunities, technological transformation, reading culture, and family discussion. The literatures used in this review were published and unpublished articles, reports, and working papers from Google Scholar, PubMed, MedRxiv, BioRxiv, and official websites of national and international organizations.Keywords: challenges, opportunities, silver linings, Ethiopia, coronavirus disease, COVID-19